Consistent daily activity patterns across tropical forest mammal communities - Vargas, Andrea Vallejo; Sheil, Douglas; Semper-Pascual, Asunción; Beaudrot, Lydia; Ahumada, Jorge; Bitariho, Robert; Espinosa, Santiago; Estienne, Vittoria; Jansen, Patrick; Kayijamahe, Charles; Martin, Emanuel; Lima, Marcela; et al. (Research square, 2022)
Most animals follow distinct daily activity patterns reflecting their adaptations1, requirements, and Interactions 2-4. Specific communities provide specific opportunities and constraints to their members that further shape these patterns3,4. Here, we ask whether community-level diel activity patterns among long-separated biogeographic regions differ or converge and whether the resulting patterns indicate top down (predation risk) or bottom-up processes (prey availability)? We estimated the diel activity of ground dwelling and scansorial mammals in 16 protected areas across the tropics, using an extensive network of camera traps, and examined the relationship to body mass and trophic guild. We found that mammalian guilds exhibited consistent diel activity patterns across regions, indicating similar responses to similar evolutionary and ecological opportunities and constraints. Larger herbivores tended to be more nocturnal than smaller herbivores, whereas carnivores and omnivores showed the opposite pattern. Insectivores were exceptions, revealing regional differences in which larger insectivorous species were more nocturnal than smaller ones in the Afrotropical and Indo-Malayan regions, while the pattern reversed in the Neotropics. The consistent contrast between predators and prey suggests that diel activity within these communities is primarily determined by large predators and associated risk of predation